2014
DOI: 10.1017/s0958344014000421
|View full text |Cite
|
Sign up to set email alerts
|

Computer-mediated input, output and feedback in the development of L2 word recognition from speech

Abstract: This paper reports on the impact of computer-mediated input, output and feedback on the development of second language (L2) word recognition from speech (WRS). A quasi-experimental pre-test/treatment/ post-test research design was used involving three intact tertiary level English as a Second Language (ESL) classes. Classes were either assigned to a control group (n = 31) or to one of two alternative treatment levels which used a web-based computer application enabling self-determined opportunities to repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…For example, since L2 learners' ability to recognise words from speech is crucial to L2 listening comprehension, Hulstijn (2003) has suggested taking advantage of multimedia software to develop L2 learners' vocabulary knowledge for L2 listening comprehension. Subsequent studies indicate that such computer-mediated approaches contribute positively to improving L2 vocabulary knowledge and L2 listening comprehension (Matthews, Cheng, & O'Toole, 2015;Matthews & O'Toole, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, since L2 learners' ability to recognise words from speech is crucial to L2 listening comprehension, Hulstijn (2003) has suggested taking advantage of multimedia software to develop L2 learners' vocabulary knowledge for L2 listening comprehension. Subsequent studies indicate that such computer-mediated approaches contribute positively to improving L2 vocabulary knowledge and L2 listening comprehension (Matthews, Cheng, & O'Toole, 2015;Matthews & O'Toole, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for providing the initial letters of the target word was to ensure that only the target words were elicited. The ProOrth vocabulary The instrument used to measure ProPhon vocabulary knowledge was a partial dictation test Matthews, Cheng & O'Toole, 2015) which requires test takers to produce a single target word after listening to a spoken stimulus sentence once (See Figure 3). This test format taps the test taker's ability to recognize the phonological form of the target word and produce that target word in the written form.…”
Section: Testing Productive/orthographic (Proorth) Vocabulary Knowledgementioning
confidence: 99%
“…Social Science Learning Education Journal 03 (8) phonological vocabulary size on scores investigated in small sample size 30 students of EFL to measure both orthographic and phonological vocabulary size and the results of the participants' sub-skill scores from IELTS. This study showed there was a strong correlation between phonological vocabulary size and listening scores.…”
Section: Investigated the Role Of Word Knowledge Includingmentioning
confidence: 99%
“…The previous research revealed the importance of WRS as component of spoken language processing and the foundation of listening comprehension. 8 continuously explored suggestive previous result of the effectiveness of computer-mediated approaches which facilitate increased levels of exposure to input, increased production of output, and the delivery of feedback. Receptive vocabulary knowledge test and word recognition test were used, and it revealed that the use of the application, either with or without text feedback, was associated with significant improvements in L2 WRS and positive effects in intervention target words.…”
Section: Word Recognition From Speech In L2 Listeningmentioning
confidence: 99%